Role of oxygen functional groups in graphene oxide for reversible room-temperature NO2 sensing. (September 2015) - Choi, You Rim; Yoon, Young-Gui; Choi, Kyoung Soon; Kang, Jong Hun; Shim, Young-Seok; Kim, Yeon Hoo; Chang, Hye Jung; Lee, Jong-Heun; Park, Chong Rae; Kim, Soo Young; Jang, Ho Won
Abstract: Reduced graphene oxide (rGO) is one of the promising sensing elements for high-performance chemoresistive sensors because of its remarkable advantages such as high surface-to-volume ratio, outstanding transparency, and flexibility. In addition, the defects on the surface of rGO, including oxygen functional groups, can act as active sites for interaction with gaseous molecules. However, the major drawback of rGO-based sensors is the extremely sluggish and irreversible recovery to the initial state after a sensing event, which makes them incapable of producing repeatable and reliable sensing signals. Here, we show that pristine GO can be used as the active sensing material with reversible and high response to NO2 at room temperature. First-principles calculations, in conjunction with experimental results, reveal the critical role of hydroxyl groups rather than epoxy groups in changing metallic graphene to the semiconducting GO. We show that the adaptive motions of the hydroxyl groups, that is, the rotation of these groups for the adsorption of NO2 molecules and relaxation to the original states during the desorption of NO2 molecules, are responsible for the fast and reversible NO2 sensing behavior of GO. Our work paves the way for realizing high-response, reversible graphene-based room-temperature chemoresistive sensors for further functional convergence.